Evaluation of Ultrasound-Guided Erector Spinae Plane Block for Intraoperative Hemodynamic Stability and Postoperative Pain Relief in Laparoscopic Cholecystectomy: A Randomized Controlled Trial - Dr. Kalyani Pimpale; Dr Alpa Sonawane; Dr. Dinesh Kumar Sahu; Dr Rashmi Verma, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Laparoscopic cholecystectomy, although minimally invasive, frequently provokes sympathetic surges during pneumoperitoneum and significant early visceral pain, necessitating opioids that delay recovery. The ultrasound-guided erector spinae plane block (ESPB) has emerged as a simple interfascial technique with paravertebral spread that might blunt these responses. Objective: To evaluate whether pre-incision bilateral ESPB enhances intra-operative haemodynamic stability and reduces opioid consumption and early pain after laparoscopic cholecystectomy. Methods: Sixty adults (ASA I–II) scheduled for elective laparoscopic cholecystectomy were randomly assigned to receive either bilateral ESPB at T7 with 20 mL of 0.25% bupivacaine per side combined with standard general anesthesia (ESPB group, n = 30) or general anesthesia alone (Control, n = 30). Hemodynamic parameters—heart rate (HR), systolic and diastolic blood pressure (SBP, DBP), and mean arterial pressure (MAP)—were recorded. Fentanyl boluses were administered if there was a 20% increase from baseline in heart rate or mean blood pressure. Total intraoperative fentanyl consumption was documented. If heart rate or mean blood pressure remained more than 20% above baseline, a 20 mg bolus of propofol was given. In resistant cases, where fentanyl and propofol were ineffective, 0.5 mg IV boluses of metoprolol were administered, and the total amount given was recorded. Postoperatively, patients were monitored for pain using a Numerical Rating Scale (NRS) at 30 minutes, and at 1, 2, 4, 8, and 12 hours. If the NRS score exceeded 4, 1 mg/kg IV tramadol was administered. Adverse events were noted. Results: The groups were similar in age, sex, ASA class, and surgical duration. ESPB resulted in lower HR from 10 to 90 minutes after pneumoperitoneum (p < 0.05). No significant differences were observed in mean SBP and DBP at any time point (p > 0.05) between the groups. The mean MAP difference was not statistically significant, except at 5 and 60 minutes (p < 0.05). Cumulative intraoperative fentanyl (116.7 ± 24.0 µg vs. 131.7 ± 24.5 µg; p = 0.02) and propofol supplementation (17% vs. 50%; p = 0.013) were reduced, along with metoprolol use (10% vs. 40%; p < 0.01). Postoperative tramadol requirement decreased by 42% (p < 0.01), and NRS scores were significantly lower at 0.5, 2, 4, 8, and 12 hours (p < 0.05). Shoulder-tip pain and nausea were lower but not statistically different. Conclusions: Pre-operative bilateral ESPB provides significant hemodynamic stability. This stability is demonstrated by a notable decrease in intraoperative fentanyl use, anesthetic needs, and vasodepressor requirements compared to the control group, along with superior early analgesia without additional complications. Incorporating ESPB into enhanced recovery pathways for laparoscopic cholecystectomy may hasten ambulation and discharge.